Effects of different rest intervals in high intensity interval training programs on VO2max, body composition, and isokinetic strength and power - KAYHAN, RECEP FATİH (My University, 2024)
The aim of this study was to evaluate the effect of 8 weeks of short and long rest running-based high-intensity training (HIIT) on body composition, isokinetic strength, and maximal oxygen uptake (VO2max). Nineteen physically active men were recruited to voluntarily participate in the study. The participants were grouped using the closed-envelope randomized method as HIIT with a short rest (HIITS, n = 9; age: 19.60 ± 1.34 years) and HIIT with a long rest (HIITL, n = 10; age: 19.77 ± 0.97). Pre and post the 8-week running-based HIIT program, body mass index and body fat % were measured and all subjects performed isokinetic strength tests to determine their hamstring (H)/quadriceps (Q) peak torque ratio and the peak power and peak work for their H and Q muscles. The participants also underwent a graded exercise test to determine their VO2max. Statistical analysis performed with One-Way Variance Analysis and Bonferroni correction post hoc tests. As a result of the study, there were no significant differences between the pre- and post-training isokinetic strength parameters for the H and Q of HIITL and HIITS at velocities of 60 and 240◦s−1. The VO2max did not change for HIITS training but the VO2max increased (p < 0.05) for HIITL training. In conclusion, that HIITL and HIITS programs for 8 weeks did not change the relative and absolute strength, force production and the VO2max, but the VO2max increased (p < 0.05) for HIITL training. Keywords Peak torque; Peak power; Peak work; VO2max; H/Q ratio
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; H/Q ratio; Peak power; Peak torque; Peak work; VO2max